2017
DOI: 10.18632/oncotarget.15981
|View full text |Cite
|
Sign up to set email alerts
|

The hypoxia signalling pathway in haematological malignancies

Abstract: Haematological malignancies are tumours that affect the haematopoietic and the lymphatic systems. Despite the huge efforts to eradicate these tumours, the percentage of patients suffering resistance to therapies and relapse still remains significant. The tumour environment favours drug resistance of cancer cells, and particularly of cancer stem/initiating cells. Hypoxia promotes aggressiveness, metastatic spread and relapse in most of the solid tumours. Furthermore, hypoxia is associated with worse prognosis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 164 publications
3
24
0
Order By: Relevance
“…We have further demonstrated that residual leukemic bone marrow cells in a syngeneic AML model remain hypoxic after chemotherapy ( 59 ). Altogether these data support the pivotal role of hypoxia signaling in leukemias ( 60 ). Albeit our conclusions in the current study are limited to demonstrating the utility of complex I inhibition in alleviating the leukemic BM hypoxia, this finding may ultimately lead to important translational implications to be tested in subsequent studies.…”
Section: Discussionsupporting
confidence: 75%
“…We have further demonstrated that residual leukemic bone marrow cells in a syngeneic AML model remain hypoxic after chemotherapy ( 59 ). Altogether these data support the pivotal role of hypoxia signaling in leukemias ( 60 ). Albeit our conclusions in the current study are limited to demonstrating the utility of complex I inhibition in alleviating the leukemic BM hypoxia, this finding may ultimately lead to important translational implications to be tested in subsequent studies.…”
Section: Discussionsupporting
confidence: 75%
“…Hypoxia is also present in bone marrow hematopoietic niches where B lineage cells reside [15]. Therefore, in this study, we analyzed the effects of hypoxia on CD19 CAR-T cells [16,17] and B cell maturation antigen (BCMA) CAR-T cells in vitro [18].…”
Section: Introductionmentioning
confidence: 99%
“…Foam-based 3D culture similar to fiber scaffolds [16] increased the resistance of the leukaemia cell lines to inhibitory effects of imatinib and to the maintenance of AML cells [29,30] and also selects bortezomib-resistant CML stem cells [31]. It has been shown that 3D-cultures are better than 2D-cultures in simulating important tumor characteristics in vivo such as hypoxia and resulting drug resistant phenotype [32].…”
Section: Discussionmentioning
confidence: 99%